ANALISIS RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR - Dian Efriyenty (Yayasan Akrab Pekanbaru, 2018)
This research is expected by investors to get long-term benefits by obtaining dividends. In this era of globalization, the economy is increasingly unstable. Where the weakening value of investment in Indonesia and the instability of the dollar against the rupiah. In investing, investors must have a goal to get the return they expect. But there are also investors who want short-term profits that can be obtained by getting capital gains. So that investors who have such goals see the development of fluctuations in the market. Lack of information obtained by investors in conducting analysis will result in inappropriate decisions in making investment decisions. Investors must consider and understand the company's financial statements and ratios that can help ease investment, including financial ratios that calculate expected returns. The fundamental and technical information can be used as a basis for investors to predict returns. Risk or uncertainty with one of the considerations is financial ratio. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange, with sampling from several criteria. The sample of this study is 65 manufacturing companies from 2013 to 2017. The results of the study state that partially the current ratio, total debt to equity ratio, total asset turnover, earnings per share, return on assets have a significant effect on stock returns. While the simultaneous current ratio, total debt to equity ratio, total asset turnover, earnings per share, return on assets have a significant effect on stock returns.